Characteristics of a hydraulic jump in Bingham fluid - Shu, Jian Jun (2011)
Hydraulic jump taking place in Bingham fluid over a horizontal plate has been studied. The formulas for conjugate depths, bottom shear stress and critical depth are established. Since no exact analytical solution in closed form can be obtained for conjugate depths, an approximate formula is developed. This formula can provide good results with an error less than 4%. The analytical results reveal that the critical depth and the ratio of conjugate depths increase until the bottom shear stress exceeds a certain value and then decrease afterwards. The bottom shear stress downstream of hydraulic jump is smaller than that upstream. The results are verified by experimental data and observations available in the literature.